2015
DOI: 10.2147/rip.s71454
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines and drugs against Neospora caninum, an important apicomplexan causing abortion in cattle and other farm animals

Abstract: Abstract:The apicomplexan parasite Neospora caninum represents an important abortioncausing parasite in cattle. The economic impact of neosporosis has led to considerable investments to develop vaccines that would prevent infection and abortion. Live-attenuated vaccines have been shown to confer some protection against N. caninum infection, but may cause problems due to regulatory issues and other drawbacks. Therefore, efforts have been undertaken to develop recombinant subunit vaccines based on antigens invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Numerous previous studies have revealed the efficient potential of NcSAG1 in stimulating cellular or humoral immune responses [reviewed thoroughly by Hemphill and Müller (2015) ; Aguado-Martinez et al (2017) ; Sinnott et al (2017) ; Fereig and Nishikawa (2020) ]. However, the immunomodulatory effect of NcSAG1 is more likely relevant to the cellular than the humoral immune response ( Kato et al, 2015 ; Marin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have revealed the efficient potential of NcSAG1 in stimulating cellular or humoral immune responses [reviewed thoroughly by Hemphill and Müller (2015) ; Aguado-Martinez et al (2017) ; Sinnott et al (2017) ; Fereig and Nishikawa (2020) ]. However, the immunomodulatory effect of NcSAG1 is more likely relevant to the cellular than the humoral immune response ( Kato et al, 2015 ; Marin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…While it is logical to assume that essential protein-coding genes implicated in parasite virulence have been identified, the sheer number of unclassified or hypothetical regions cannot be neglected or deemed unimportant, prompting this study. Current vaccine candidates for parasites within this phylum involve either surface or secreted antigens that appear to be fundamental to parasite invasion, the mechanisms and contributors of which appear to be mostly conserved (Kim and Weiss, 2004;Hemphill, 2015). Consequently, the identification and investigation of uncharacterised proteins through sequence homology, structure, and known hallmarks of parasite virulence, has the power to perpetuate the discovery of targets for vaccine development.…”
Section: Introductionmentioning
confidence: 99%